Upaya Penanganan Bullying Melalui Penanaman Pendidikan Karakter (Studi Kasus di Kelas IV SD Muhammadiyah 4 andangsapi Surakarta Tahun Ajaran 2016/2017) - Inayah, Nurul; Dra. Risminawati, Dra. Risminawati M.Pd (2017)
This study aims to describe: 1. The forms of bullying that occur in the fourth grade of elementary school Muhammadiyah 4 Kandangsapi Surakarta, 2. The factors that influence the occurrence of bullying in the fourth grade of elementary school Muhammadiyah 4 Kandangsapi Surakarta, 3. Planting implementation of character education in elementary school Muhammadiyah Surakarta 4 kandangsapi, 4. The efforts to tackle bullying through the cultivation ofcharactereducation in elementary school Muhammadiyah 4 Kandangsapi Surakarta. This research is a qualitative case study design (case study). A resource in this research is the principal, IV A classroom teacher, IV B grade teacher, a teacher of Religion, an English teacher, and students of IV grade. Data collection techniques uses an interviews, observation, and documentation. Data analysis performs interactively on, data reduction, data display, and conclusion. The validity of data is done through triangulation and triangulation techniques. The results shows the existence of other forms of bullying that occur in the fourth grade of elementary school Muhammadiyah 4 Kandangsapi Surakarta. The forms of bullying that occur in the fourth grade is divided into three forms, forms of physical bullying include hitting, kicking, pushing, and garroting neck. Forms of verbal bullying, taunting them, saying gross, cheering, and surname. While the form of mental bullying form of exclusion, and threatening. Planting implementation of character education in elementary school Muhammadiyah Surakarta 4 Kandangsapi namely through the integration of character values in teaching and learning activities, through extracurricular activities, through the culture of the school. Efforts to tackle the teachers in the form of call, advising, faced to the principal for students involve in bullying even calling parents if bullying problems are difficult to overcomeKeywords: bullying, character education, handling.